ANALISIS FAKTOR YANG MEMPENGARUHI WISATAWAN MANCANEGARA MEMILIH MODA TRANSPORTASI SEPEDA MOTOR DI KAWASAN KUTA SELATAN - Sena, I Made Aswin Ananta; Wijaya, N.M.S.; Dewi, N.G.A.S. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021), 2021)
The study aims to analyze the factors that affect tourist in choosing a motorcycle as a mode of transportation in South Kuta area. Data were collected using survey online questionnaires. The number of respondents was 100 international tourists. The methodologies used were descriptive statistics, factor analysis using the IBM SPSS 26.0 for Windows application. The result of the study shows that there are two factors, which influence international tourists to choose the motorcycle as the transportation mode in South Kuta area. The two factors are external and internal factors. The external factor consists of the street width, the convenience of renting the transportation mode, availability of the parking area, the traffic density, the transportation cost, and the reliability. The internal factor are family recommendation, easy to used, own a driving license, budget, and driving range. Based on the result of factor analysis, the external factor as a dominant factor that influences international tourists to choose motorcycle as transportation mode in South Kuta Area.